Personal Characteristics Of The Teacher In Music Teaching - Najibullo Ergashev (Euro Asian Journal Publishing, 2024)
This article is aimed at showing the role of the pedagogue's personal characteristics in music education, and it provides information about the requirements placed on the personality of a music teacher to ensure the effectiveness of his work. Also, the effectiveness factors of the music teacher's activity are pedagogical abilities, perceptive abilities of the teacher from the characteristics of communication, indicators of his pedagogical orientation, as well as professional important pedagogical qualities, readiness for pedagogical creativity, professional knowledge and experience acquired by him. the importance of skills is highlighted.
Keywords: Music; pedagogical skills; orientation